Lore and the Process of Tradition: Locating the Place of Belief Narratives in Ka Phur Nongjri and Sohbar - Japang, Auswyn Winter (Ethnographica et Folkloristica Carpathica, 2021)
Since the earliest times, the villages of Nongjri and Sohbar, located in the Southern Khasi Hills of North-Eastern India, have had their own religious ceremonies, customs, ways of behaving and beliefs that they share in their practice and narration. Their beliefs in certain village deities are linked with the well-being of the entire village, and are said to have existed from the time these villages were established. In the beliefs of the inhabitants of Nongjri and the village of Sohbar, the deities, manifest themselves in various performances and folksongs, and therefore, have become part of the performance itself. Deities, often in the form of human beings, engage in conversation with the villagers. Folklore also tells us that during festivities the approval of the celebrations by village deities becomes the key aspect to foretell the particular nature of the coming year. The lore gathered from the places considered for this study would provide us with a new perspective on belief narratives existing in the Khasi community, while continually locating the position of lore and various processes of tradition in the socio-cultural and religious milieu of both Nongjri and Sohbar. The narratives explored in this paper will also provide – in the Khasi cultural context – the essence of War-Khasi beliefs and rituals that have remained largely undocumented.